Comparison of morphemic word structure and a cartographic sign - Živković Dragica; Jovanović Jasmina (Glasnik Srpskog Geografskog Društva, 2011)
Language is a system of gestures, sounds, characters, symbols and words that are used to display concepts and communication. Map language is derived from natural language, rather than parallel to it, as its graphical equivalent. Natural and mapping language is based on a system of signs. In the natural language, the letters are the smallest units, and arranged meaningfully they constitute a sign - a word i.e. a concept. In a cartographic language one sign is one term. But common to both languages is the basis of character - morphemes and its accessories - affixes, which in the cartographic language have greater possibilities of expression.